The Day the Dog Said, "Cock-a-Doodle Doo! - David McPhail (New York, United States Scholastic US, 1997)
On an odd day at the barnyard, the animals get mixed up, and soon the duck is "mooing," the goose is "oinking," and the dog is "cock-a-doodle-dooing." Original. Reading level, 1.8.
Keywords: Level Reader -- Level Reader